2021
DOI: 10.3390/ma14205914
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Metal Matrix Composites Based on CrxNiy-TiN for Additive Technology

Abstract: The novelty of this work consists of obtaining original fundamental data on the laws of synthesis of new metal matrix composite materials for additive technologies. CrN + TiNi composites were obtained using the method of self-propagating high-temperature synthesis. In this work, analysis of the parameters of the synthesis of composite materials as well as their structure and phase composition were carried out. A scheme for the formation of a composite structure is established; it is shown that the phase compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 38 publications
5
13
0
Order By: Relevance
“…On the other hand, the use of such a material may be impractical in conditions where the requirements for physical and mechanical characteristics are less stringent. In [22], composite metal-matrix CrNi-TiN materials were obtained from a CrN-TiNi powder mixture by self-propagating high-temperature synthesis. The authors of the above paper have found that the particles of the CrNi-TiN composite SHS-fabricated powder, similar to (Ni-Ti)-TiB 2 , consist of a matrix (CrNi) and ceramic particles (TiN).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the use of such a material may be impractical in conditions where the requirements for physical and mechanical characteristics are less stringent. In [22], composite metal-matrix CrNi-TiN materials were obtained from a CrN-TiNi powder mixture by self-propagating high-temperature synthesis. The authors of the above paper have found that the particles of the CrNi-TiN composite SHS-fabricated powder, similar to (Ni-Ti)-TiB 2 , consist of a matrix (CrNi) and ceramic particles (TiN).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, their mechanical properties have to be studied both at room temperature and at elevated temperatures. It must also be noted that in [17,18,22], laboratory-fabricated composites were used and those were produced from pressed workpieces with a weight of ≤25 g, a diameter of ≤23 mm, and a height of ≤40 mm. Meanwhile, a transition from laboratory-based fabrication to industrial-scale fabrication entails changes in the synthesis conditions that may affect the phase composition and structure of final SHS products.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works [24,25], we obtained composite powder materials, CrNi-TiN and (Ni-Ti)-TiB 2 , from CrN-TiNi and NiB-Ti powder mixtures using self-propagating high-temperature synthesis (SHS). The structure of these powders consisted of a CrNi/Ni-Ti intermetallic matrix wherein TiN/TiB 2 particles were evenly distributed.…”
Section: Introductionmentioning
confidence: 99%
“…The particle size varied from 0.1 to 4 µm, and their average size was 0.57 µm. In another study [ 10 ], we synthesized composite structured particle powders of CrNi-TiN using the SHS method. The particle structure consisted of titanium nitride (TiN) ceramic inclusions, which were uniformly distributed throughout the CrNi intermetallic matrix.…”
Section: Introductionmentioning
confidence: 99%
“…CrNi-TiN powders were successfully used as feedstock for the production of composite materials by direct laser growth. The hardness of such materials is higher than the hardness of analogues obtained from Inconel powder [ 10 ]. In [ 9 , 10 ], the authors found that ceramic particles in the metal matrix composites of CrNi-TiN and (Ni-Ti)-TiB 2 were formed during SHS (in situ) due to exothermic reactions of the initial components of the NiB-Ti and CrN-TiNi powder mixtures.…”
Section: Introductionmentioning
confidence: 99%